Evaluation of Knowledge, Attitude and Practices about Hospital Waste Management in Sanitary Workers of DHQ Hospital Bhakkar - Suleman, Muhammad Talha; Suleman, Bushra (International Journal of Research in Counseling and Education, 2023)
Abstract: Objective: To ascertain the existing level of knowledge, attitude and practices about hospital waste management in sanitary workers working in a secondary care hospital of Bhakkar.Methodology: It was a cross sectional study held on 1st August to 31 August 2017. The universe of the study was 108 sanitary workers of DHQ Hospital Bhakkar. The data was collected with the help of a semi structured questionnaire after taking an informed consent and then analyzed by SPSS version 21. Direct observations were also made to assess the segregation practices, collection of waste, and usage of PPEs, transportation, onsite storage and disposal strategy of healthcare waste (HCW).Results:  Among 108 sanitary workers, 87 %(n=94) were male and 13 %(n=14) were female. Mean age of respondents was 29.2 years with a standard deviation of 9.0 years.  24.1 %(n=26) were illiterate while 75.9 %(n=74) were literate.Level of knowledge was good in 2.78 %(n=3) respondents, average in 22.22 %(n=24) respondents, poor in 75.0 %(n=81) respondents. With respect to practices, it was good in 8.33 %(n=9) respondents, average in 67.59 %(n=73) respondents, poor in 24.07 %(n=26) respondents.The hospital was using “three bins system” for waste segregation. The PPE usage, waste segregation and transport were not up to the standards. Open fire burning followed by land disposal was the final disposal strategy. The general waste was carried away by TMA for final disposal. Conclusion: This study pointed out serious gaps in the awareness and practices such as: usage of PPEs, transport, storage and disposal of healthcare waste. These issues can be overcome by sensitizing the medical community, training of staff and allocating the sufficient funds.Keywords: Healthcare waste, sanitary workers, Knowledge, Practices, Segregation, Collection, Transport, Disposal